REPRESENTASIPEREMPUAN DALAM IKLAN CITRA DI MEDIA CETAK (Studi Analisis Semiotika lklan Pemutih Kulit CITRA , Edisi 2-15 Januari 2008 di Majalah Smart CHIC) - Pratiwi, Ayuningtyas (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
The use of mass media become a tool of the most effective, efficient and quick way to inform the company in a product  or service to the society s,  and was mostly  done  by the  company  to  rnenggunakan rnassa  media as  a  tool  to promote products or services to be offered to the public, one of which is print media that this is a magazine in ha]. Most magazines are published mernang comfort women. One reason is because this segment is potential for pernasaran certain products such as cosmetics, clothing, accessories,furniture, cleaning tools rurnah, and others.  Womenhave  all the beauty that can be used as an advantage to attract anyone who saw  it. Startingfrom   the long black  hair, beautiful face,  smooth,  tall, slim body  and  smooth-skinned  and white.  The author would like to investigatefurther how a beauty product,  in this  case, Citra Body Lotion, representingthe woman as a model of beauty advertising.